Information systems project teams: factors for high performance - Moura, Isabel Cristina A. A. (2019)
Purpose The purpose of this research is twofold: identify and gain a better insight on factors that can influence high performance of Information Systems (IS) project teams from the perspective of IS professionals (i.e. team members and leaders), and thus contribute to the general discussion on high-performance project teams; and offer both IS project team members and their project managers some feedback on how to build and manage teams more constructively and to enhance team performance in today's demanding business environment. Design/methodology/approach The authors used an exploratory case study of a small-size holding company and a qualitative analysis of the data to address the research questions. Findings Results show a set of perceived factors that can influence high team performance in IS projects. Participants' perceptions barely coincide. For instance, mutual trust was the only factor suggested as facilitating high team performance by 5 participants (out of 13). Differences may be because of participants' characteristics (e.g. time on the job). All perceived factors are classified in the literature as nontechnical (i.e. having to do with behavioral and/or socio-organizational matters of project management). Originality/value This paper is among the very few empirical studies consolidating knowledge on high-performance IS project teams (e.g. it is still unclear if there are IS project team-specific factors that influence high performance). For the highly technical IS industry, this study came across human-centric factors transversal to different project teams.